2012
DOI: 10.1371/journal.pone.0039548
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Degradation of PrPSc by a Protease Secreted from Aeropyrum pernix K1

Abstract: BackgroundAn R30 fraction from the growth medium of Aeropyrum pernix was analyzed for the protease that can digest the pathological prion protein isoform (PrPSc) from different species (human, bovine, deer and mouse).Methodology/Principal FindingsDegradation of the PrPSc isoform by the R30 fraction and the purified protease was evaluated using the 6H4 anti-PrP monoclonal antibody. Fragments from the N-terminal and C-terminal of PrPSc were also monitored by Western blotting using the EB8 anti-PrP monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 50 publications
2
30
0
Order By: Relevance
“…W226 (Petsch et al, 2011) binds to C-terminal domain of PrP C (epitope: 145-155), whereas SAF34 (Perrier et al, 2004) and EB8 (Didonna et al, 2015;Snajder et al, 2012) bind to N-terminal domain of PrP C (epitope: 59-89 and 26-34, respectively). Anti-NCAM antibodies (AB5032 from Millipore) were used in local delivery and immunocytochemical experiments.…”
Section: Antibodiesmentioning
confidence: 99%
“…W226 (Petsch et al, 2011) binds to C-terminal domain of PrP C (epitope: 145-155), whereas SAF34 (Perrier et al, 2004) and EB8 (Didonna et al, 2015;Snajder et al, 2012) bind to N-terminal domain of PrP C (epitope: 59-89 and 26-34, respectively). Anti-NCAM antibodies (AB5032 from Millipore) were used in local delivery and immunocytochemical experiments.…”
Section: Antibodiesmentioning
confidence: 99%
“…Prions can cause transmissible spongiform encephalopathies of brain and nervous system including bovine spongiform encephalopathy, scrapie and Creutzfeldt-Jakob disease. Some bacterial and archaeal keratinases hydrolyze not only the hard-degrading keratinous fiber but also digest the protease resistant aggregated prion proteins (Mitsuiki et al, 2006;Šnajder et al, 2012;Suzuki et al, 2006;Gupta et al, 2013). Keratinase from strain PWD-1, a serine protease of a moderate thermophile Bacillus licheniformis (Lin et al, 1992) was the first reported protease capable of degrading the prions.…”
Section: Bio-safety On Infectious Prion Proteinsmentioning
confidence: 99%
“…Keratin and keratinase as well as keratinolytic microorganisms have tremendous applications in various sectors including biodegradation and waste management, biotechnology and industry, cosmetic and pharmaceutical products and medical treatments (Mitsuiki et al, 2006;Šnajder et al, 2012;Suzuki et al, 2006;Gupta et al, 2013). This review presents keratinase producing microorganisms with an emphasis on thermophiles.…”
Section: Introductionmentioning
confidence: 99%
“…Prion strains differ in many aspects: by their biochemical profiles and characteristics, like differences in band pattern in electrophoresis, resistance to proteinase-K digestion and altered amino-terminal proteinase-K cleavage sites, also resulting in different antibody binding patterns. Additionally, they differ regarding their efficiency of transmission, differences in species barrier, the length of incubation time, pattern and intensity of brain lesions and clinical symptoms, different immune response, and stability (Solforosi et al, 2013;Šnajder et al, 2012;Hamir et al, 2011;Černilec et al, 2007;Telling, 2004). In sheep, for instance, we recognise at least ten ovine scrapie strains (Moore et al, 2016;Benestad et al, 2008;Morales et al, 2007;Bossers et al, 2000).…”
Section: Prion Strains and Transmissibilitymentioning
confidence: 99%